2021
DOI: 10.1002/cyto.a.24500
|View full text |Cite
|
Sign up to set email alerts
|

Optical section structured illumination‐based Förster resonance energy transfer imaging

Abstract: Förster resonance energy transfer (FRET) microscopy is an important tool suitable for studying molecular interactions in living cells. Optical section structured illumination microscopy (OS‐SIM), like confocal microscopy, has about 200 nm spatial resolution. In this report, we performed quantitative 3‐cube FRET imaging in OS‐SIM mode and widefield microscopy (WF) mode, respectively, for living cells expressing FRET constructs consisting of Cerulean (C, donor) and Venus (V, acceptor). OS‐SIM images exhibited hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…imaged biomolecular interactions in the membrane‐associated cytoskeleton of a neuron with high optical resolution (Szalai et al., 2021). Although Structured Illumination Microscopy (SIM) improves optical resolution by only a factor of two, recent application of SIM with FRET made it possible to determine FRET in live HeLa cells with reasonable optical resolution (Liu et al., 2022). Improving SIM could provide an attractive and simple alternative approach to enhance the resolution of FRET images.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…imaged biomolecular interactions in the membrane‐associated cytoskeleton of a neuron with high optical resolution (Szalai et al., 2021). Although Structured Illumination Microscopy (SIM) improves optical resolution by only a factor of two, recent application of SIM with FRET made it possible to determine FRET in live HeLa cells with reasonable optical resolution (Liu et al., 2022). Improving SIM could provide an attractive and simple alternative approach to enhance the resolution of FRET images.…”
Section: Applicationsmentioning
confidence: 99%
“…FRET in live HeLa cells with reasonable optical resolution (Liu et al, 2022). Improving SIM could provide an attractive and simple alternative approach to enhance the resolution of FRET images.…”
Section: Szabó Szöllősi and Nagymentioning
confidence: 99%
“…Some other attractive quantitative cell analysis methods have been reported in nanotechnology. Chen et al [16] showed the use of Forster Resonance Energy Transfer (FRET) imaging with optical section structure illumination microscopy for the analysis of living cells. With a home‐built stochastic optical reconstruction microscopy (STORM), Qu et al [17] explored the nanoliposome fine structures that may aid the development of liposome‐based photodynamic therapy for cancer treatment.…”
Section: Figurementioning
confidence: 99%
“…This method, called structured illumination-based super-resolution Förster resonance energy transfer microscopy (SIM-FRET), enables dynamic SR quantitative FRET imaging of living cells. 11,12 SIM-FRET achieves high spatiotemporal resolution and minimal photodamage while remaining compatible with commonly used fluorescent protein FRET pairs for conventional live-cell FRET imaging. [12][13][14] Although SIM-FRET has demonstrated its capability to quantify FRET analysis in living cells, the accuracy of quantitative analysis is still greatly affected by SIM reconstruction artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 SIM-FRET achieves high spatiotemporal resolution and minimal photodamage while remaining compatible with commonly used fluorescent protein FRET pairs for conventional live-cell FRET imaging. [12][13][14] Although SIM-FRET has demonstrated its capability to quantify FRET analysis in living cells, the accuracy of quantitative analysis is still greatly affected by SIM reconstruction artifacts. To maintain the fidelity of image intensity, SIM-FRET has conventionally employed linear Wiener reconstruction for SR image reconstruction.…”
Section: Introductionmentioning
confidence: 99%